DIVERSIFICATION OF RICE (ORYZA SATIVA L.) BASED CROPPING SYSTEMS FOR HIGHER PRODUCTIVITY IN NORTH COASTAL ZONE OF ANDHRA PRADESH - U. SAI SRAVAN; MURTHY, K. V. RAMANA (The Bioscan, 2014)
Field investigation was conducted at Agricultural College Farm, Naira on sandy clay loam soil during pre kharif, kharif and rabi 2012-2013. The experiment was laid out in randomized block design, with four replications and seven cropping systems. Sunnhemp, greengram, blackgram, sesame, clusterbean and bhendi during pre kharif, rice during kharif and rice fallow blackgram during rabi were tried. Sunnhemp as pre kharif crop has produced significantly highest crop residues on fresh weight basis (30.11 t ha-1) and dry matter (13096 kg ha-1) than other pre kharif crops while clusterbean was significantly inferior for both crop residues on fresh weight basis (1.16 t ha1) and dry matter (446 kg ha-1). Incorporation of different crop residues significantly altered the growth and development of kharif rice. Crop residue incorporation of sunnhemp produced significantly highest dry matter production at harvest (14455 kg ha-1), panicles m-2 (265), filled grains panicle-1 (128), 1000 grain weight (24.33 g) and yield (6501 kg ha-1) of kharif rice followed by greengram while lowest dry matter production at harvest (7754 kg ha-1), panicles m-2 (204), filled grains panicle-1 (100), 1000 grain weight (21.95 g) and yield (4125 kg ha-1) was recorded with that of fallow. Post harvest soil OC (0.39%), available nitrogen (215.33 kg ha-1), available phosphorus (20.83 kg ha-1) and available potassium (256.99 kg ha-1) improved with sunnhemp crop residue incorporation. Seed (382 kg ha-1) and haulm (743 kg ha-1) yield of rice fallow blackgram was found to be significantly superior with incorporation of sunnhemp crop residue while inferior seed and haulm was with fallow (225 and 462 kg ha-1 respectively). Productivity was the highest with bhendi-rice-rice fallow blackgram (9265 kg ha-1), while sunnhemp improved both rice and rice fallow blackgram yields and hence sunnhemp -rice-rice fallow blackgram was suggested for North Coastal Zone of Andhra Pradesh.